001.5 An australia-wide molecular study of neisseria gonorrhoeae identifies frequent occurrence of a key cephalosporin resistance mechanism. (13th September 2015) - Trembizki, E; Regan, DG; Donovan, B; Chen, MY; Guy, RJ; Lahra, MM; Whiley, D
Abstract : Background: Neisseria gonorrhoeae (NG) antimicrobial resistance (AMR) has been declared an urgent threat by the United States Centres for Disease Control and Prevention. Ceftriaxone is the mainstay of treatment, however many specific NG strains throughout the world exhibit decreased susceptibility (DS) and, occasionally, high-level resistance. In particular, this emerging resistance has been associated with an NG strain of multi-locus sequence type (MLST) 1901 and harbouring a 'mosaic' Penicillin Binding Protein sequence (mPBP2–1901). Here, we sought to measure the prevalence of this strain in Australia. Methods: In the context of the Gonorrhoea Resistance Assessment by Nucleic Acid Detection (GRAND) study, we developed molecular NG-AMR detection methods to test 2225 NG isolates collected in the first half of 2012 from around Australia. These isolates comprised approximately 90% of all NG isolates collected for culture-based AMR testing, and about 30% of all NG diagnoses nationally. The isolates were characterised using the Sequenom iPLEX platform to provide both an MLST type and AMR mutation data. We compared the findings to minimum inhibitory concentration (MIC) results from culture-based AMR surveillance. Results: We identified 186 distinct NG genotypes among the 2225 isolates; the 8 most common comprised 51% of all isolates. The mPBP2–1901 strain was the second most prevalent genotype, accounting for 8.4% (188/2228) of isolates. The prevalence of mPBP2–1901 was highest in Victoria and New South Wales (12% and 10.2%, respectively) compared to the other states (all <4.3%). Of the 188 mPBP2–1901 strains, 64% were classified as sensitive to ceftriaxone by culture (MIC ≤0.03 mg/L) and 36% as DS (MIC0.06 – 0.125 mg/L). Conclusion: These findings highlight that a small number of genotypes account for the majority of NG infections in Australia, with the mPBP2–1901 strain accounting for 8% of isolates. The findings also demonstrate the benefits of using molecular testing to complement phenotypic NG AMR surveillance. Disclosure of interest statement: Nothing to Declare.